Reduction of CD44+/CD24− breast cancer cells by conventional cytotoxic chemotherapy - Aulmann, Sebastian; Waldburger, Nina; Penzel, Roland; Andrulis, Mindaugas; Schirmacher, Peter; Sinn, Peter (Human pathology, 2010)
Breast cancer cells with the CD44+/CD24− phenotype have been associated with stem cell properties. To analyze effects of cytotoxic chemotherapy on these cells, we examined a series of 50 breast carcinomas before and after neoadjuvant chemotherapy with epirubicin/cyclophosphamide using double immunofluorescence. Before treatment, an average of 4.4% of the tumor cells displayed a CD44+/CD24− phenotype. However, after chemotherapy, the frequency of CD44+/CD24− cells dropped to 2% (P = .008). To test this unexpected finding, we analyzed a second collective of 16 patients that preoperatively had received either 4 cycles of doxorubicin/pemetrexed, followed by 4 cycles of docetaxel or 4 cycles of doxorubicin/cyclophosphamide, followed by 4 cycles of docetaxel with similar results (8.7% CD44+/CD24− cells on average before and 1.1% after chemotherapy). In addition, no association was observed between the frequency of CD44+/CD24− cells and the response to chemotherapy or patient survival. However, patients with tumors containing high numbers of CD44+/CD24− cells more frequently developed bone metastases in the course of disease. In conclusion, our findings challenge the proposed role of CD44+/CD24− cells as cancer stem cells in tumor resistance to chemotherapy as they apparently are not selected by conventional cytotoxic agents.
Online verfügbar 11 Dezember 2009
Im Titel sind die Zeichen + und - hochgestellt
Gesehen am 28.11.2022